Study preferred alignments of angular momentum vector of i – magnitude SDSS galaxies having redshift 0.54 – 0.60 - Sah, Shiv Shankar Prasad; Yadav, Shiv Narayan (BIBECHANA, 2022)
We present a study of the three-dimensional orientation of spin vector of i – magnitude having higher redshift ranging from 0.54 to 0.60 with respect to the equilateral co-ordinate system. The main aim of this work is to know the orientation and projection of the spin vector of distant galaxies. The database is taken from SDSS 14th data release (DR-14) and this redshift range contains 239,209 galaxies. SDSS provides two – dimensional observed data, we convert it into three-dimension rotation axes of the galaxy with the help of the ‘position angle inclination method’. The expected isotropy distribution curves are obtained by removing the selection effects and performing a random simulation generating 107 virtual galaxies. To check, isotropy or anisotropy we have to carry out four statistical tests: chi-square, auto-correlation coefficient, first-order Fourier series, and First-order Fourier probability. In the study, we observed random orientation of spin vector of galaxies in all twenty samples and supported a strongly Hierarchy model of galaxy evolution. Also, the projection of spin vector is found to be isotropic in samples i01, i02, i03, i16, i17, i18, i19, and i20 and the remaining samples i04 to i15 are seen as local anisotropic due to the merging phenomenon of galaxies and tidal effect. This shows the problem in a coordinate system.BIBECHANA 19 (2022) 68-74